Impaired prenylation of Rab GTPases in the gunmetal mouse causes defects in bone cell function - Taylor, Adam (Landes Bioscience, 2011)
Vesicular trafficking is crucial for bone resorption by osteoclasts, in particular for formation of the ruffled border membrane and for removal of the resultant bone degradation products by transcytosis. These processes are regulated by Rab family GTPases, whose activity is dependent on post-translational prenylation by Rab geranylgeranyl transferase (RGGT). Specific pharmacological inhibition of RGGT inhibits bone resorption in vitro and in vivo, illustrating the importance of Rab prenylation for osteoclast function. The gunmetal (gm/gm) mouse bears a mutation in the catalytic subunit of RGGT, causing a loss of 75% of the activity of this enzyme and hence hypoprenylation of several Rabs in melanocytes, platelets and cytotoxic T cells. We have now found that prenylation of several Rab proteins is also defective in gm/gm osteoclasts. Moreover, while osteoclast formation and cytoskeletal polarization occurs normally, gm/gm osteoclasts exhibit a substantial reduction in resorptive activity in vitro compared with osteoclasts from +/gm mice, which do not have a prenylation defect. Surprisingly, rather than the osteosclerosis that would be expected to result from defective osteoclast function in vivo, gm/gm mice exhibited a slightly lower bone mass than +/gm mice, indicating that defects in other cell types, such as osteoblasts, in which hypoprenylation of Rabs was also detected, may contribute to the phenotype. However, gm/gm mice were partially protected from ovariectomy-induced bone loss, suggesting that levels of Rab prenylation in gm/gm osteoclasts may be sufficient to maintain normal physiological levels of activity, but not pathological levels of bone resorption in vivo.